Identifikasi Mineral Pasir Tiga Warna Pantai Puntaru Kabupaten Alor-NTT - Martasiana Karbeka; Herianus Manimoy; Bertho A Abolasinga (Jurnal Kimia Fullerene, 2021)
Puntaru beach is famous for its three-colored sand that is mixed into one of them reddish-brown, black, and white sand. Research on the mineral composition of the tricolor sand has been conducted so that the use of three-colored sand is still done traditionally. This study aims to obtain information on the silica content and other mineral compositions of the three-colored sand of Puntaru Beach as initial data for further development. The three-color sand preparation process is carried out by the method of milling / crushing sand samples then sieving and washing with H2O. Stages of characterization of silica in three-colored sand were carried out using X-ray fluorescence (XRF), X-ray powder diffraction (XRD), and Fourier-transform infrared (FTIR). The analysis showed that the percentage of Si was the most dominant 45.28%, followed by Fe 25.94% and other minor elements. XRD results show that the three-colored sand contains quartz mineral (SiO2) identified at the main peak with 2 with in the 24.34 Ã‚Â° area. The black color of the sand is influenced by Fe content of 25.94% with hematite metal oxide (Fe2O3) 15.80% and reddish-brown influenced by the presence of sulfur (3.25%) in the form of mineral SO3 4.32%.